Pengaruh Karakteristik Perusahaan Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan (CSR) Pada Perusahaan Yang Terdaftar Di Indeks LQ45 Bursa Saham Indonesia (BEI) - Rony Arthana; Djuma hir (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
In the era of globalization, environmental awareness has brought about changes in attitudes towards profit orientation of the social orientation of the company. Management as the agent can not avoid the reality of the impact of corporate activity that not only generate profits / raise stock prices, but also have environmental impacts such as damage to ecosystems, pollution, and so forth. The purpose of this study was to analyze the influence of firm characteristics on corporate social responsibility disclosure in corporate annual reports in Indonesia. The population in this study are 10 companies listed in the LQ45 index of Indonesian Stock Exchange (IDX) with the research period of 2007 until 2011 and meet the criteria established. Analysis of the data used is multiple linear regression. The results of this study indicate that public ownership, liquidity, and firm size have no significant effect on corporate social responsibility disclosure. Meanwhile leverage and profitability have a significant effect on corporate social responsibility disclosure. Keywords: corporate social responsibility disclosure, public ownership, leverage, liquidity, profitability, and firm size.